ANALISIS ATAS PELAKSANAAN FUNGSI PENGAWASAN PENGELOLAAN KEUANGAN DAERAH OLEH ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN PUNCAK JAYA - Wonda, Iskandar; Karamoy, Herman; Ilat, Ventje (Universitas Sam Ratulangi, 2013)
The purpose of this study is to analyze the local financial management supervision by the local parliament members period 2009-2014 in Puncak Jaya regency and stuff underlying onset of these conditions. The data used in this research were the primary data using the instrument as a list of questions with in-depth interviews to the research informants. The subjects were legislators of Puncak Jaya Regency period of 2009-2014 totaling 24 people. The method used were qualitative descriptive analysis.The results showed that the personal background would have less effect on the function of supervision of local financial management. The political background effect on the supervisory function of financial management at Puncak Jaya Regency legislators. The legislator knowledge about the budget effect to a good supervision of the local financial management. The legislator who have a good understanding of the local financial regulatory would easy to supervise whether the budget has been run according to predetermined objectives and to detect the occurrence of budget leaks.Keywords: Personal Background, Political Background, Legislators Knowledge about the Budget, Supervisory Function of the Local Financial Management by the Local Legislators.